Effect of Coenzyme-Q10 on Doxorubicin-Induced Nephrotoxicity in Rats - Azza A. K. El-Sheikh; Mohamed A. Morsy; Marwa M. Mahmoud; Rehab A. Rifaai; Aly M. Abdelrahman (Advances in Pharmacological Sciences)
Nephrotoxicity is one of the limiting factors for using doxorubicin (Dox) as an anticancer chemotherapeutic. Here, we investigated possible protective effect of coenzyme-Q10 (CoQ10) on Dox-induced nephrotoxicity and the mechanisms involved. Two doses (10 and 100 mg/kg) of CoQ10 were administered orally to rats for 8 days, in the presence or absence of nephrotoxicity induced by a single intraperitoneal injection of Dox (15 mg/kg) at day 4 of the experiment. Our results showed that the low dose of CoQ10 succeeded in reversing Dox-induced nephrotoxicity to control levels (e.g., levels of blood urea nitrogen and serum creatinine, concentrations of renal reduced glutathione (GSH) and malondialdehyde, catalase activity and caspase 3 expression, and renal histopathology). Alternatively, the high dose of CoQ10 showed no superior nephroprotection over the low dose, as there were no significant improvements in renal histopathology, catalase activity, or caspase 3 expression compared to the Dox-treated group. Interestingly, the high dose of CoQ10 alone significantly decreased renal GSH level as well as catalase activity and caused a mild induction of caspase 3 expression compared to control, probably due to a prooxidant effect at this dose of CoQ10. We conclude that CoQ10 protects from Dox-induced nephrotoxicity with a precaution to dosage adjustment.